1, 2‐Diaryl‐2‐hydroxyiminoethanones as Dual COX‐1 and β‐Amyloid Aggregation Inhibitors: Biological Evaluation and In Silico Study. (11th October 2014) - Irannejad, Hamid; Unsal Tan, Oya; Ozadali, Keriman; Dadashpour, Sakineh; Tuylu Kucukkilinc, Tuba; Ahangar, Nematollah; Ahmadnejad, Mahsa; Emami, Saeed
<x xml:space="preserve">Abstract</x> To find out new agents for treating inflammatory‐involved diseases such as Alzheimer's disease, a series of 1, 2‐diaryl‐2‐hydroxyiminoethanones containing vicinal diaryl pharmacophore of COX inhibitors were tested by a set of in vitro, in vivo, and computational studies. The in vivo study of compounds indicated their prominent anti‐inflammatory ability at the doses of 10 and 20 mg/kg comparable to celecoxib (10 mg/kg). Further in vitro COX‐1/COX‐2 evaluations revealed that 4‐methoxy derivative 3 had a high selective COX‐1 inhibitory activity (COX‐1, IC50 = 0.12 μm, SI > 833). To evaluate their potential use against Alzheimer's disease, in vitro evaluation of β‐amyloid fibril formation using Aβ(1–40) and Aβ(1–42) peptides was performed. The evaluation of their antiaggregation ability gave impressive results and comparable to rifampicin and indomethacin. Conformational study of compound 3 and subsequent docking of its restrained analogs on both active sites of COX‐1 and COX‐2 could provide a proof of its COX‐1 selectivity as well as molecular dynamic simulation could elucidate and give more insight into the amyloid disaggregation mechanisms leading to rational design of inhibitors.